HERMES: Using Commit-Issue Linking to Detect Vulnerability-Fixing Commits - Nguyen-Truong, Giang; Kang, Hong Jin; Lo, David; Sharma, Abhishek; Santosa, Andrew E.; Sharma, Asankhaya; Ang, Ming Yi (2022 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER), 2022)
Software projects today rely on many third-party libraries, and therefore, are exposed to vulnerabilities in these libraries. When a library vulnerability is fixed, users are notified and advised to upgrade to a new version of the library. However, not all vulnerabilities are publicly disclosed, and users may not be aware of vulnerabilities that may affect their applications. Due to the above challenges, there is a need for techniques which can identify and alert users to silent fixes in libraries; commits that fix bugs with security implications that are not officially disclosed. We propose a machine learning approach to automatically identify vulnerability-fixing commits. Existing techniques consider only data within a commit, such as its commit message, which does not always have sufficiently discriminative information. To address this limitation, our approach incorporates the rich source of information from issue trackers. When a commit does not link to an issue, we use a commit-issue link recovery technique to infer the potential missing link. Our experiments are promising; incorporating information from issue trackers boosts the performance of a vulnerability-fixing commit classifier, improving over the strongest baseline by 11.1% on the entire dataset, which includes commits that do not link to an issue. On a subset of the data in which all commits explicitly link to an issue, our approach improves over the baseline by 12.5%.